Verbal behavior: What is really researched? An analysis of the papers published in TAVB over 30 years. Issue 2 (2nd July 2016) - Presti, Giovambattista; Moderato, Paolo
ABSTRACT: Skinner sensed that Verbal Behavior was his most important work and his conceptual framework gave birth to a healthy body of theoretical and empirical contributions, since the end of the 1960s, with an acceleration in the mid 1980s, probably due among other factors to a dedicated journal, The Analysis of Verbal Behavior (TAVB). Following recent analyses on the experimental literature on verbal operants and given the absence of previous analyses on the body of TAVB publications, a thorough examination of the papers published on TAVB was conducted, as a proxy to the field, to understand which parts of Skinner's taxonomy of verbal operants generated experimental data and how empirical models may influence the way the field progresses. Strong trends in research with few elementary verbal operants emerged, posing some questions on the ease of experimental models and the biases that this work can generate in the field.